Sistem bantuan keputusan penempatan dan pertukaran guru (SBKPPG) untuk pejabat pendidikan daerah (PPD) - Wang, Chih Fong (2005)
One of the factors that affect the quality of education system is the matching of a teacher’s professional opsyen with subject taught in school. The match is not easy because organisational requirements and individual needs often conflict with each other. Teachers need to work in a place that suits his or her needs. Currently placement of teacher is done manually. This research developed a Decision Support System for Transfer and Placement of Teachers for the District Education Office (SBKPPG). The system is a combination of four sub systems, which are SisBSKG-Sekolah for collections of data on teachers requirement at school level, SisTukar_Guru for the transfer applicants, SisTukar_Sekolah for schools to compile the transfer applications from teachers and SisBSKG-PPD for the District Education Office to integrate the data from the three subsystems and analyse the requirements by district, by zone, by school or by subject level. The sub systems can function independently, but fully integrate at data level. The development of the system took into consideration the decision process of the organisation, work process, data required, analysis that needs to be done for a decision on the placement of a teacher. Needs requirement analysis was done through interviews, research on document and current systems. The system developed helps to improve the efficiency and effectiveness of current process. The decision model that ranks transfer applicants by priorities, interfaces that integrate schools requirements with teachers’ expertise and process that facilitates data entries help the PPD improve the matching of teacher’s options with subjects taught in school. This will help to improve the quality of teaching and learning in class through time.